Understanding and preventing hit-and-run driving: a crime script analysis. Issue 1 (February 2018) - Hopkins, Matt; Chivers, Sally
Abstract Although a small body of research has explored drivers' decisions to leave the scene of a road traffic collision (hit-and-run), little research has explored how understanding the processes of hit-and-run collisions could inform prevention strategies. Drawing upon findings from a literature review and in-depth interviews with 52 convicted hit-and-run drivers, a crime script approach is utilised as a heuristic device to explore the precursors, immediate aftermath and longer-term aftermath of hit-and-run events. This method allows for motivational factors to be identified. Then, utilising Clarke's techniques of situational crime prevention as a guiding framework, possibilities for the prevention of hit-and-run are presented.